2010
DOI: 10.1016/j.ccr.2010.11.024
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive Canonical NF-κB Activation Cooperates with Disruption of BLIMP1 in the Pathogenesis of Activated B Cell-like Diffuse Large Cell Lymphoma

Abstract: SUMMARY Diffuse large B-cell lymphoma (DLBCL) comprises disease entities with distinct genetic profiles, including germinal center B-cell (GCB) like and activated B-cell (ABC) like DLBCLs. Major differences between these two subtypes include genetic aberrations leading to constitutive NF-κB activation and interference with terminal B-cell differentiation through BLIMP1 inactivation, observed in ABC- but not GCB-DLBCL. Using conditional gain-of-function and/or loss-of-function mutagenesis in the mouse we show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
192
1
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 179 publications
(213 citation statements)
references
References 36 publications
13
192
1
7
Order By: Relevance
“…BLIMP1 mutations are frequently found in activated B cell (ABC)-like DLBCL, 45,46 and it has been demonstrated that BLIMP1 functions as a tumor suppressor. 46,47 Let-7a, miR-9, miR-125b have been shown to regulate BLIMP1 expression, 17,48,49 and miR-9 was reportedly increased in FL tissue samples and in germinal center B cells. 17,20 A similar pattern was observed in our study; we found that let-7a and miR-9 were over-expressed in FL tumor cells with down-regulation of BLIMP1.…”
mentioning
confidence: 99%
“…BLIMP1 mutations are frequently found in activated B cell (ABC)-like DLBCL, 45,46 and it has been demonstrated that BLIMP1 functions as a tumor suppressor. 46,47 Let-7a, miR-9, miR-125b have been shown to regulate BLIMP1 expression, 17,48,49 and miR-9 was reportedly increased in FL tissue samples and in germinal center B cells. 17,20 A similar pattern was observed in our study; we found that let-7a and miR-9 were over-expressed in FL tumor cells with down-regulation of BLIMP1.…”
mentioning
confidence: 99%
“…It is already clear that dramatically increased numbers of marginal zone B cells in knock-in mice constitutively expressing IKK␤ (35) and phospho-mimetic activation loop IKK␤ knock-in mice cause lymphomagenesis (14). Although TALEN-or CRISPRbased mutagenesis has not yet been reported in genetic studies of cancer, we establish here that this is a powerful approach that can be employed in the study of tumorigenesis.…”
Section: Discussionmentioning
confidence: 90%
“…Serine 181 in the activation loop of IKK␤ is the crucial residue that needs to be phosphorylated by an upstream kinase for it to switch to its active conformation (13). A phospho-mimetic mutation in serine 181 can lead to constitutive activation of IKK␤, and constitutively activated IKK␤ can contribute to lymphoma generation in transgenic mice (14). Lysine 171, however, is situated parallel to serine 181 in the activation loop, and no structural models or experimental data exist to indicate whether the cancer-associated alterations found in this residue of IKK␤ activate or inactivate this critically important kinase, or if these changes represent functionally irrelevant "passenger" mutations.…”
mentioning
confidence: 99%
“…Une inactivation de ce gène (mutations, délétions, répres-sions transcriptionnelles) est retrouvée chez 50 % des patients atteints de lymphome diffus à grandes cellules de type activé [78][79][80][81], et son rôle suppresseur de tumeur a été formellement montré dans ces lymphomes diffus en utilisant des modèles murins d'invalidation de PRDM1 [80,81]. Ce gène jouerait également un rôle important dans l'homéostasie T et la tolérance du soi [82,83].…”
Section: Translocationunclassified